Variation in spikelet fertility and grain quality under heat stress during reproductive stage in Thai non-photosensitive rice (Oryza sativa L.) cultivars - Malumpong, C.; Siriya, N.; Pompech, D.; Itthisoponkul, T.; Arikit, S.; Romkaew, J.; Cheabu, S. (International Journal of Agricultural Technology, 2020)
The averaged daytime temperature is 40 ºC during reproductive stage of rice production in dry season, Thailand leading to spikelet sterility and grain yield reduction. The total of 27 non-photosensitive rice cultivars together with a heat tolerant cultivar (M9962) and a susceptible cultivar (Sinlek) were investigated under high temperature (40-45 °C) during 6 hr daytime for heat tolerance during reproductive stage in dry season in the year of 2017 and 2018. The selected top four cultivars and other 6 lines/cultivars were validated again under high temperature in dry season in the year of 2019. The results of screening and yield trials in 2017-2018 revealed that most of Thai cultivars were ranged from susceptible to high temperatures during the reproductive stage. The top four cultivars showing the greatest heat stress seeds in 2017 and 2018 were SPB2, RD41, Bahng Taen (BT) and SPB60 cultivars. In 2019, these four cultivars showed high performance of seed production under high temperature, and the genetic relationship of SPB2, RD41 and BT were closely related to M9962. However, BT showed good grain quality in heat stress, especially in the chalky trait. In conclusion, the four cultivars can be promoted to grow in dry season as moderately heat tolerant cultivars. Moreover, these cultivars would be useful for breeding programmes to improve heat tolerance in terms of yield and grain quality.